The East German church and the end of communism - Burgess, John P. 1954- (Oxford Univ. Press, 1997)
This book addresses the role of religion in the massive political changes that took place in Eastern Europe in 1989. In particular, it examines the role played by the East German church in that country's bloodless revolution. Drawing on his own research in East Germany and relying primarily on sources published in East Germany itself, author John Burgess demonstrates the roots of the church's theology in Barth, Bonhoeffer, and in the Barmen declaration, which in 1934 pronounced Christianity and Nazi ideology to be incompatible. He explores how the dissident groups drew on church symbols and language to develop a popular alternative theology, and finally shows how the theological tension between the church and the dissidents provided impulses for political democratization. It should be of great interest to scholars of theology, church history, political science, and twentieth-century European history.